Propuesta de una campaña comunicacional de valores por medio del humor no violento, en la carrera de comunicación social de la UTC - Trávez Ortiz, Omar Gustavo (2016)
This research aims to facilitate education in values through communication and humor to the formation of the university community. Reflection on values education is proposed, from the imagination in which the formative historical and ethical sense stands. The basis of the research is theoretical and is validated by experts. Also it carried out a reflection on the possibility of raising an education supported by the myths and legends, independent of any ideology or belief values. The analysis of the results serve as a basis for critical reflection on the practice of education….